2022
DOI: 10.1007/s11412-022-09365-x
|View full text |Cite
|
Sign up to set email alerts
|

‘Supporting socially shared regulation during collaborative task-oriented reading’

Abstract: This study examined how to improve students’ regulation of task-oriented reading (TOR). TOR encompasses reading and information processing needed to perform a specific task. Previous studies suggest students can benefit from a collaboration script to enhance socially shared regulation of TOR. The collaboration script elicits discussions about task perception, strategy selection, and strategy reflection. This study aimed to examine the depth and socially sharedness of metacognitive regulation when working with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…However, it is important to note that this study only scratches the surface of SSRL at the cognitive level. SSRL is a multifaceted phenomenon that involves cognition (Kielstra et al, 2022), emotion (Nguyen et al, 2022), motivation (Järvelä et al, 2008), and behaviour. Future research can explore SSRL and collaborative programming learning from different angles to gain a more comprehensive understanding of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that this study only scratches the surface of SSRL at the cognitive level. SSRL is a multifaceted phenomenon that involves cognition (Kielstra et al, 2022), emotion (Nguyen et al, 2022), motivation (Järvelä et al, 2008), and behaviour. Future research can explore SSRL and collaborative programming learning from different angles to gain a more comprehensive understanding of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Think aloud studies have shown evidence of differing degrees of task awareness through its influence on processes such as the selection of task relevant text (e.g., Schellings and Broekkamp, 2011 ). Other work has measured different aspects of a learners’ task understanding using task grounded questions given before, during, or after engaging in the task (e.g., Schraw, 1998 ; Miller, 2009 ; Oshige, 2009 ; Rivera-Reyes et al, 2016 ; Schoor et al, 2021 ; Kielstra et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study suggest that if doing so prompts students to be more aware of the task, then their performance on the task will benefit. Indeed, questions and checklists given prior to reading can encourage readers to elaborate their task models and increase task performance (e.g., Ayroles et al, 2021 ; Kielstra et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have found that learners have difficulties achieving most of these tasks, including setting goals, monitoring and controlling, and reflecting and evaluating. Previous studies have employed different approaches to facilitate socially shared regulation, such as collaboration scripts (Kielstra et al, 2022), developing socially shared regulation tools (Järvelä et al, 2015), and peer assessment (Lin, 2018). However, very few studies compared how different learning approaches promote socially shared regulation in online collaborative learning context.…”
Section: Literature Reviewmentioning
confidence: 99%